Phygital Transformation and the Modern Customer of Luxury Fashion - Kovář, Jan (2023)
This thesis explores the integration of phygitisation, a blend of physical and digital experiences, in the luxury fashion industry, examining its impact on modern consumer engagement. Confirmatory factor is used as the method to validate the structural model established in the theoretical part of the thesis. The findings reveal challenges and opportunities in balancing digital integration with maintaining brand exclusivity. The results of this thesis provide practical implications for new luxury communication strategie.